2020
DOI: 10.1002/adem.202000170
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering and Direct Observation of Strengthening Behavior in Field‐Sintered Boron Nitride Nanotube–Magnesium Alloy Composite

Abstract: Boron Nitride Nanotube (BNNT) is integrated in AZ31 magnesium alloy by field-assisted powder metallurgy route. A mat of BNNT is sputter-coated with pure Mg and then sandwiched between AZ31 alloy powders. This layered composite is consolidated by spark plasma sintering. A high processing pressure of 400 MPa aids in intimate alloy-nanotube adhesion due to localized deformation. Thermal diffusion between AZ31 and BNNT (at 400°C sintering temperature) results in the formation of Mg 3 N 2 and AlN nano-phases at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Destructive testing, which involves using lab-type instrumentation that requires a specific sample preparation and geometry, is mainly performed to characterize the mechanical properties of materials [14][15][16][17][18][19][20][21]. It has also been used to characterize the curing kinetics of polymeric materials.…”
Section: Introductionmentioning
confidence: 99%
“…Destructive testing, which involves using lab-type instrumentation that requires a specific sample preparation and geometry, is mainly performed to characterize the mechanical properties of materials [14][15][16][17][18][19][20][21]. It has also been used to characterize the curing kinetics of polymeric materials.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14,15 ] This makes BNNT a highly suitable candidate for engineering metal matrix composites as metal manufacturing processes typically involve exposure to elevated temperatures. Fabrication of BNNT‐reinforced aluminum and magnesium composites has been reported via magnetron sputtering, [ 16 ] ion implantation, [ 17 ] powder metallurgy, [ 18–23 ] solidification, [ 24,25 ] mechanical working, [ 26,27 ] and thermal spray [ 28 ] routes. These studies have demonstrated promising improvements in elastic modulus, [ 22,28 ] hardness, [ 18–21,28 ] and strength [ 18,19,21,22,24,26,27 ] of metal matrices due to BNNT addition.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] In addition to the proven thermal and oxidation stability of BNNTs (up to 900 C in air), these nanostructures have shown extensive damage tolerance at temperatures of 250-500 C. [18,19,23,24] The addition of BNNTs as reinforcing nanoparticles in low-melting-point metal matrices such as aluminum and magnesium has resulted in composites with competitive moduli, fracture strength, and unique deformation mechanisms under tension and compression. [5,9,10,21,[25][26][27][28][29] A key challenge in the integration of BNNTs to Ti matrices lies in control over the interfacial interactions between the nanotube and the matrix during sintering. A thin reaction layer (%5-10 nm) [30] will aid in increasing bonding strengths and promote the effective transfer of stresses.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18,19,23,24 ] The addition of BNNTs as reinforcing nanoparticles in low‐melting‐point metal matrices such as aluminum and magnesium has resulted in composites with competitive moduli, fracture strength, and unique deformation mechanisms under tension and compression. [ 5,9,10,21,25–29 ]…”
Section: Introductionmentioning
confidence: 99%